The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/catal12111422
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathway of Phenol Degradation of a Cold-Adapted Antarctic Bacteria, Arthrobacter sp.

Abstract: Phenol is an important pollutant widely discharged as a component of hydrocarbon fuels, but its degradation in cold regions is challenging due to the harsh environmental conditions. To date, there is little information available concerning the capability for phenol biodegradation by indigenous Antarctic bacteria. In this study, enzyme activities and genes encoding phenol degradative enzymes identified using whole genome sequencing (WGS) were investigated to determine the pathway(s) of phenol degradation of Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Aerobic processes are characterized by lower cost and higher degradation efficiency due to microorganisms’ rapid growth and ability to completely mineralize the xenobiotics [ 40 ]. For instance, some characteristic strains that utilize the aerobic catabolism of phenols belong to the genera of Acinetobacter , Pseudomonas , Rhodococcus , and Kocuria [ 2 , 3 , 10 , 41 ] while phenol-degrading strains that belong to the Arthrobacter genus are particularly few [ 17 , 19 , 20 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerobic processes are characterized by lower cost and higher degradation efficiency due to microorganisms’ rapid growth and ability to completely mineralize the xenobiotics [ 40 ]. For instance, some characteristic strains that utilize the aerobic catabolism of phenols belong to the genera of Acinetobacter , Pseudomonas , Rhodococcus , and Kocuria [ 2 , 3 , 10 , 41 ] while phenol-degrading strains that belong to the Arthrobacter genus are particularly few [ 17 , 19 , 20 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Lee et al suggested the ortho pathway for phenol degradation in psychrotolerant Arthrobacter sp. strains, which was validated from both the bioinformatic analysis and enzyme assays of catechol 1,2-dioxygenase and catechol 2,3-dioxygenase [ 20 ]. On the contrary, Karigar et al reported the utilization of a meta -cleavage pathway for phenol degradation in Arthrobacter citreus , based on enzyme activities of phenol hydroxylase and catechol dioxygenases combined with metabolites identification through TLC [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold-adapted enzymes C 12 O and C 23 O enzymes have been found in several cold-adapted phenol-degrading strains. 26 It is reported that cold-adapted enzymes have ten-fold greater activity at low temperatures (below 20–30 °C) compared to their mesophilic counterparts. 27 Most of the cold-adapted enzymes have high specific activity below 20–30 °C, and some enzymes such as a novel-hormone sensitive lipase (HSL) family IV cold-adapted esterase (EstN7) and the psychrophilic BpL5 (a corresponding enzyme isolated from the arctic bacterium B. pumilus ) can retain the maximum activity in 5 °C.…”
Section: Microorganisms Cold-adapted Mechanismmentioning
confidence: 99%
“…However, new technologies are being developed in high -throughput sequencing, which provides high quality data with short or long read sequences. To date, several genomes from psychrophilic bacteria and archaea have been sequenced (Pucciarelli et al, 2015;Ramasamy et al, 2019;John et al, 2020;Wang et al, 2021;Lee et al, 2022;Riccardi et al, 2022;Otur et al, 2023). The advantage of whole genome sequencing of Antarctic bacteria is to analyze and characterize the genes in the entire genome, especially genes coding industrially relevant enzymes using DNA sequencing methods and bioinformatics tools (assemble and analyze the structure and functions of specific gene).…”
Section: Advanced Strategies To Study Antarctic Bacterial Adaptation ...mentioning
confidence: 99%